Human Cattle: Prison Overpopulation and the Political Economy of Mass Incarceration - Hanna, Peter (2016)
This paper examines the costs and impacts of prison overpopulation and mass incarceration on individuals, families, communities, and society as a whole. We start with an overview of the American prison system and the costs of maintaining it today, and move on to an account of the historical background of the prison system to provide context for the discussions later in this paper. This paper proceeds to go into more detail about the financial and social costs of mass incarceration, concluding that the costs of the prison system outweigh its benefits. This paper will then discuss the stigma and stereotypes associated with prison inmates that are formed and spread through mass media. The stigma and stereotypes propagated by the media result in a negative social construction of prison inmates, contributing to a culture of incarceration that makes it difficult to end America’s dependence on prisons. The final section of the paper discusses the challenges that come with changing the culture of incarceration, which include the deep entrenchment of said culture and the self-perpetuating nature of many of the problems associated with prison, and offers possible alternatives and solutions to incarceration and the problems associated with it